Ende des regionalen Experiments? Eine Bilanz der Reform des englischen Planungssystems unter New Labour - Grohs, Stephan (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
The English planning system underwent a series of remarkable reforms under the New Labour governments between 1997–2010. After the hollowing out of planning functions under the previous conservative governments, planning regained a new significance on the political agenda. First, there was a turn from the traditional paradigm of land-use-planning to a more strategically oriented Spatial Planning approach. Second, the institutional landscape was subjected to a far-reaching reallocation of competences between the local and the revalued regional level. The article resumes this process which was stopped abruptly after the change in government of 2010. It analyzes the implementation of the reforms drawing on two in depth case studies. An evaluation of the reforms identifies the strengths and also the obstacles of the far-reaching transformation in the highly politicized English planning landscape. A discussion of the future of planning after the preliminary end of the regional experiment concludes this article.
Keywords: Planning; Regional planning; United Kingdom; Administrative reform; Regionalisation; Implementation